PERFORMANCE ANALYSIS OF FOUR-POINT EGAOR ITERATIVE METHOD APPLIED TO POISSON IMAGE BLENDING PROBLEM - Eng, Jeng Hong; Saudi, Azali; Sulaiman, Jumat (Malaysian Journal of Science, 2019)
Poisson image blending is one of the useful editing tools in image processing to generate a desirable image which is impossible to acquire. The key to this solution is to obtain the unique solution of Poisson equation. Thus, the motivation of this paper is to examine the effectiveness of 4-EGAOR iterative method to solve the linear system generated from the Poisson image blending problem. To evaluate its effectiveness, the formulation and implementation of 4-EGAOR, SOR and AOR iterative methods are demonstrated. The numerical results revealed that 4-EGAOR iterative method improved the computational time taken and reduced the number of iterations used. In fact, the new images generated by the proposed block iterative method give a satisfactory visual effect.